The world's end [videorecording (DVD)] - Wright, Edgar, 1974-; Pegg, Simon, 1970-; Pegg, Simon, 1970-; Frost, Nick, 1970-; Freeman, Martin, 1971-; Considine, Paddy (Universal Studios Home Entertainment, 2013)
Twenty years after attempting an epic pub crawl, five childhood friends reunite when one of them becomes hellbent on doing it again. They are convinced by mate Gary King, who drags his reluctant pals to their hometown to once again attempt to reach the fabled pub called The World's End. As they attempt to reconcile the past and present, they realize the real struggle is for the future, not just theirs but humankind's. Reaching the pub is the least of their worries.